Long-term effect of food insecurity on body weight gain and metabolic risk in a context of high socioeconomic vulnerability in a medium-income country: the SANCuité cohort, Brazil, 2011–2022 - Laurentino, Jackson Silva Lima; Martins-Costa, Isadora Macedo de Oliveira; Oliveira-Silva, Rônisson Thomas de; Santos, Ana Beatriz Macêdo Venâncio dos; Palmeira, Poliana de Araújo (Frontiers in Public Health, 2025)
ObjectiveUsing longitudinal data from a study conducted in an area of high socioeconomic vulnerability in Brazil, we examined the long-term effects of food insecurity (FI) and social determinants on body weight gain (body weight, BMI) and metabolic risk (waist circumference - WC, waist-to-height ratio - WHtR) over 11 years of follow-up, conducted between 2011 and 2022.MethodsFace-to-face household interviews were conducted using the Brazilian Food Insecurity Scale to measure FI, and anthropometric measurements of weight, height, and WC were taken. Data analysis was performed in STATA 15.0 using multilevel mixed-effects regression with covariate adjustment and predicted marginal means with marginal differences.ResultsAmong the 210 individuals followed over 11 years, high prevalence of FI was observed (2011: 51.8%; 2022: 45.9%), central adiposity (2011: 83.8%; 2022: 88.6%), as well as a significant increase in the prevalence of high BMI (2011–2022: +16.7 p < 0.00), general obesity (2011–2022: +15.2 p < 0.00), and abdominal obesity (2011–2022: +0.5 p 0.02) over time. Multivariate analysis showed a positive association between BMI and body weight with mild, moderate, and severe FI after 8 and 11 years of follow-up among adults. A progressive increase in predicted body weight and BMI scores was observed among adults, with an increase of +5.6 (p 0.02) and + 2.3 (p 0.01) at the end of the follow-up, respectively, being higher in individuals with severe FI compared to those with food security. Among people ≥60 years old, WC and WHtR mean varied according to time and FI categories, with a positive association observed in mild and moderate FI, and an inverse association with severe FI at the end of the follow-up.ConclusionFI is a risk factor for long-term weight gain and obesity, particularly in vulnerable populations, highlighting the need for intersectoral public policies to ensure food and nutrition security, combat obesity, and combat the structural causes of poverty and FI.